Chesapeake Bay Impact Structure Deep Drilling Project Completes Coring - G. S. Gohn; C. Koeberl; K. G. Miller; W. U. Reimold; the Scientific Staff of the Chesapeake Bay Impact Structure Deep Drilling Project (Scientific Drilling, 2006)
No abstract available. doi:10.2204/iodp.sd.3.07.2006